ASXL1 MUTATION ANALYSIS IN CHRONIC MYELOID LEUKEMIA PATIENTS - Mohammed, Aras Rafiq; Mohamada, Dlnya Asad; Hamid, Mohammad (Journal of Sulaimani Medical College, 2023)
Background In recent years, additional sex comb-like 1 (ASXL1) gene mutations have recently been linked to several myeloid cancers. Objectives To characterize ASXL1 mutation prevalence, determine if these abnormalities might constitute a significant event in CML prognosis, and establish the correlations if these mutations are associated with CML transformation and/or imatinib (IM) resistance, Here we designed a study to investigate ASXL1 gene that is frequently mutated in myeloid malignancies and evaluated their occurrence in a well-defined group of CML patients. Patients and Methods The study population consists of 80 patients diagnosed with CML under treatment with TKI (Imatinib 400,600,800 mg/day and Nilotinib). Ten healthy subjects were checked as controls. Depending on their molecular and/or cytogenetic response, CML patients will either be classified into imatinib-resistant or imatinib-good responders. Then the DNA was extracted depending on the Salting-Out protocol. Then genome amplification was performed on exon 12 and in the HOT spot region for the detection of somatic mutations, using conventional PCR. Results Nine out of 80 CML samples (11.25%) were determined to have mutations with the ASXL1 gene. We identified a novel Mutation (c.1808_1820delCCTCCTGCCGGGG S603Ffs*96) in one of the patients that has not been reported before. We also identified three other mutations (c.1933_1934del G p.G645Wfs*12, c.2047A>G p.T683A, c.1900_1922 delAGAGAGGCGGCCACCACTGCCAT E635Rfs*15). Conclusion Our discovery of an ASXL1 mutation, a potential tumour suppressor gene, is a significant genetic aberration in CML. Our findings suggest that ASXL1 mutations are common in patients with late stages of the disease and imatinib therapy resistance.
Keywords: Leukemia; Chronic Myeloid Leukemia; CML; ASXL1; Imatinib; a Tyrosine kinase inhibitor; TKI